THE ESSENCE AND CONTENT OF A SPECIAL PERIOD IN UKRAINE - Прохоренко, Михайло Михайлович; Хлань, Валерій Михайлович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
The aim of the article: is to develop a single content of the term «special period» in Ukraine based on analysis of its components and validity period. Research methodology: the basis of the methodological base of study composed of dialectical method, analysis and synthesis method and comparative method, with the help of them the special period is clarified as a specific legal regime, the beginning and the end, its components, and also a comparing of terms «special period» was conducted, which embodied in the different Ukrainian legal acts. The study is an attempt to characterize a foreign experience of a legal regulation a special period. Summary of the research: the special period as a specific legal regime determines: 1) features of a legal status: citizens, government agency, local government, business, institutions; 2) governs the organization of Military of Ukraine activity; 3) covers the period of mobilization, military situation, wartime, partly recovery period. Discussion of the results: discussion of the problem of a special period consists in definition a legal regulation of partly recovery period and an order in introduction of war as its components. The constitutions of most countries of the world establish two regimes for the exercise of state power - normal and emergency. A state of emergency is envisaged for situations in which the normal functioning of society and the state becomes impossible. Legal regulation of this regime is a guarantee against arbitrary activity of state bodies in emergency situations and is an integral element of the legal activity of the state. Thus, in emergency regimes, the priorities of the interests of civil society change, according to which the balance of public and private interests changes in the direction of public interests, accordingly, expands the powers of public authorities, and narrows the content and scope of rights and freedoms of citizens. national interests.